Analisis Pengaruh Inflasi, Tingkat Suku Bunga, Dan Indeks Hang Seng Terhadap Indeks Harga Saham Gabungan (IHSG) Di Bursa Efek Indonesia (BEI) Periode 2011-2015 - Ahmadi, Hanif; , Drs. Sujadi, M.M (2017)
Financial asset investment in the stock market today continues to grow, an investor needs to consider several things in making investment decisions in order to benefit, one of them is to consider Composite Stock Price Index (CSPI), which is a reflection of the performance of the Indonesian Capital Market. This study aimed to examine the effect of inflation, interest rate (BI rate), exchange rates (exchange rate), and the Hang Seng Index on JCI in Indonesia Stock Exchange (BEI). The period used in this study was 5 (four) years, from 2011-2015. The analytical method used in this research is multiple linear regression analysis conducted by IBM SPSS 23 with level of significant at 0.05. Before the test multiple linear regression analysis performed classical assumption in advance so that the resulting regression equation is BLUE (Best, Linear, Unbiased, Estimator). The data used is secondary data in the form of time series such as monthly data from the years 2011-2015 for each of the study variables. In addition to assessing the goodness of fit of a model to test the coefficient of determination, F test and t test. Based on the results of data analysis concluded that inflation, interest rate (BI rate), and the exchange rate (exchange rate) does not affect the JCI. While the Hang Seng Index has positive influence on JCI. Taken together (simultaneously) inflation, interest rate (BI rate), and the Hang Seng Index significantly influence the JCI.